STRATEGI KOREA TOURISM ORGANIZATION (KTO) DALAM MENINGKATKAN KUNJUNGAN WISATAWAN INDONESIA PASCA PANDEMI COVID-19 - Nofelda, Aulya; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research examines the Korea Tourism Organization (KTO) strategy in increasing Indonesian tourist visits. The Korea Tourism Organization was formed by the South Korean Government with the main aim of developing tourism and as a source of foreign exchange for the country. The increase in Indonesian tourists to South Korea continues to occur, Indonesian people go to South Korea by visiting tourist destinations and carrying out shopping activities in this country with the products on offer. However, with the Covid-19 pandemic facing the whole world, the number of tourists has decreased throughout the world. There needs to be a strategy that must be implemented to restore the tourism sector in South Korea. This research uses a Liberalism Perspective with International Tourism Strategy Theory where strategy formulation is determined by the national interests of a country. The author uses qualitative research methods, with data collection techniques using literature studies and interviews. The results of this research show that the strategy carried out by KTO is the use of Attraction through KTO Social Media Events and the role of Hallyu to interact with Indonesian society in increasing Indonesian Tourist Visits. There is utilization of Accessibilities (Access) through KTO Collaboration with Airlines and Companies in Indonesia, in facilities and infrastructure. Then there is the use of Amenities, namely Halal Tourism and Medical Tourism. Tourism. There are Ancillary Services such as the Visit Korea Book and Korea Travel Helpline. Keywords: Korea Tourism Organization, Post-Pandemic, Covid-19, Imagine Your Korea, Ha